Pengaruh Penggunaan Lampu LED sebagai Perangkap Hama terhadap Pendapatan Petani Bawang Merah Desa Kolai Kecamatan Malua Kabupaten Enrekang: The Effect of Using LED Lights as Pest Traps on the Income of Shallot Farmers in Kolai Village, Malua District, Enrekang Regency - Abd. Rahim; Pratiwi MK; Erwin Soci (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Shallots are a type of horticultural plant that is widely cultivated and used as a source of livelihood by the people of Enrekang Regency. Shallot cultivation has challenges in the form of controlling attacks by plant-disturbing organisms (OPT) which require a large amount of money and if it is not carried out, there is a risk of reducing production yields and even causing crop failure. This study aims to determine the effect of using LED lights as pest traps on the income of shallot farmers in Kolai Village, Malua District, Enrekang Regency. The method was used to compare the income of shallot farmers before and after using LED lights. The analytical method used in this study was a non-parametric test using the paired test and using the statistical analysis tool statistical product and service solution (SPSS). The results showed that the use of LED lights in shallot fields had a significant effect on the income of shallot farmers with a significance value (Asym. Sig. (2-tailed)) < 0.05. The results of this study indicate that the use of LED lights can be used as a solution to control pests while reducing the cost of shallot production.